Investment Shocks and Macroeconomic Co-Movement - Francesco Furlanetto; Gisle James Natvik; Martin Seneca (Norges Bank, 2011)
Recent studies find that shocks to the marginal efficiency of investment are a main driver of business cycles. Yet, they struggle to explain why consumption co-moves with real variables such as investment and output, which is a typical feature of an empirically recognizable business cycle. In this paper we show that within a conventional business cycle model, rule-of-thumb consumption provides a straightforward explanation of macroeconomic co-movement after a shock to the marginal efficiency of investment.
hdl:11250/2496946
Keywords: E32; 330; investment shocks; consumption; rule-of-thumb consumers; nominal rigidities; co-movement